2022
DOI: 10.1186/s13018-022-03082-9
|View full text |Cite
|
Sign up to set email alerts
|

Risk factor analysis of disc and facet joint degeneration after intersegmental pedicle screw fixation for lumbar spondylolysis

Abstract: Background Patients who do not respond to conservative treatment of the isthmus are often treated with surgery. We used direct repair plus intersegment pedicle screw fixation for the treatment of lumbar spondylolysis. The aim of this observational study was to assess the effects of this technique and evaluate various risk factors potentially predicting the probability of disc and facet joint degeneration after instrumentation. Methods The study inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
(40 reference statements)
0
3
0
Order By: Relevance
“…The isthmus was recognized as a weak area in the lumbar spine [ 37 ]. Spondylolysis is believed to result from repetitive mechanical stress on the lower lumbar vertebrae [ 51 ]. Excessive activity and stimulation of the fractured isthmus can lead to symptoms such as pain.…”
Section: Discussionmentioning
confidence: 99%
“…The isthmus was recognized as a weak area in the lumbar spine [ 37 ]. Spondylolysis is believed to result from repetitive mechanical stress on the lower lumbar vertebrae [ 51 ]. Excessive activity and stimulation of the fractured isthmus can lead to symptoms such as pain.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study investigating the risk factors affecting the incidence of facet joint degeneration found that fixation time is a risk factor. They found that the earlier bony union occurs, and internal fixation was removed, the incidence of facet joint degeneration was lowered ( 30 ). Further studies are required to clarify the effect of intersegmental pedicle screw fixation and to evaluate various risk factors that may predict the possibility of degeneration of the intervertebral disc and facet joints.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, the intersegmental fixation device can be removed surgically as early as possible. ROM of the lumbosacral region can be restored through early functional exercise (Meng et al, 2022). Certainly, the hybrid fixation is recently proposed as a new technology combining intrasegmental fixation and intersegment fixation technology, and the material application cost is slightly higher compared with the other two technologies.…”
Section: Figurementioning
confidence: 99%